STRATEGI MANAJEMEN INOVASI DALAM MENINGKATKAN DAYA SAING ORGANISASI DI ERA DIGITAL - Yosi Zahwa Amelica; Tetti flora barutu; Ratu Arum Suci; Novi Dwi Anggita; Zahwa Roichatul Aswidah; Astrid Intan Prameswari (PT. Hasba Edukasi Mandiri, 2025)
Innovation is a crucial factor to improve the competitiveness of an organization in the ever-changing digital environment. Efficient innovation management not only focuses on the creation of new products, but also considers transformation in processes, business models, and strategies implemented. This research applies a qualitative approach through a literature review method to explore innovation management strategies that can strengthen organizational competitiveness. The findings show that organizations must adopt a culture of innovation, leverage digital technology, and collaborate with external parties to create new value. In addition, challenges such as regulatory uncertainty, skills shortages, and resistance to change must be faced to ensure success in implementing innovation strategies. With a planned and responsive approach, organizations can improve their ability to survive and thrive in a competitive global market.